Regulatory Roles of Antimicrobial Peptides in the Nervous System: Implications for Neuronal Aging - Stuart, Bradey A. R.; Franitza, Ariel L.; E, Lezi (Frontiers in Cellular Neuroscience, 2022)
Antimicrobial peptides (AMPs) are classically known as important effector molecules in innate immunity across all multicellular organisms. However, emerging evidence begins to suggest multifunctional properties of AMPs beyond their antimicrobial activity, surprisingly including their roles in regulating neuronal function, such as sleep and memory formation. Aging, which is fundamental to neurodegeneration in both physiological and disease conditions, interestingly affects the expression pattern of many AMPs in an infection-independent manner. While it remains unclear whether these are coincidental events, or a mechanistic relationship exists, previous studies have suggested a close link between AMPs and a few key proteins involved in neurodegenerative diseases. This review discusses recent literature and advances in understanding the crosstalk between AMPs and the nervous system at both molecular and functional levels, with the aim to explore how AMPs may relate to neuronal vulnerability in aging.